2017
DOI: 10.1175/jcli-d-16-0875.1
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Rivers over the Northwestern Pacific: Climatology and Interannual Variability

Abstract: Atmospheric rivers (ARs), conduits of intense water vapor transport in the midlatitudes, are critically important for water resources and heavy rainfall events over the west coast of North America, Europe, and Africa. ARs are also frequently observed over the northwestern Pacific (NWP) during boreal summer but have not been studied comprehensively. Here the climatology, seasonal variation, interannual variability, and predictability of NWP ARs (NWPARs) are examined by using a large ensemble, high-resolution at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
100
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(108 citation statements)
references
References 86 publications
8
100
0
Order By: Relevance
“…For example, atmospheric rivers have been found to be a major contributor of extreme precipitation events and flooding throughout California and the Pacific Northwest (Ralph et al, ; Dettinger et al, ). Several studies have demonstrated that various large‐scale climate modes affect the frequency and position of atmospheric rivers along the West Coast, including the AO (Guan and Waliser, ); ENSO (Guan and Waliser, ; Mundhenk et al, ; Kamae et al, ), the MJO (Ralph et al, ; Guan et al, ; Mundhenk et al, ; Mundhenk et al, ), and the PNA (Guan and Waliser, ), while it has also been shown that the relationship between the MJO and atmospheric river activity is further modulated by the phase of other HCIs, such as ENSO (Mundhenk et al, ) and the QBO (Baggett et al, ; Mundhenk et al, ). Additional investigation is required in order to shed more light on the impact of the lower‐frequency variability of the MJO, ENSO, and the EAWR, on long‐term precipitation variability along both coasts and the potential modulation of the these HCIs by the other dominant interannual modes of variability as mentioned above.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…For example, atmospheric rivers have been found to be a major contributor of extreme precipitation events and flooding throughout California and the Pacific Northwest (Ralph et al, ; Dettinger et al, ). Several studies have demonstrated that various large‐scale climate modes affect the frequency and position of atmospheric rivers along the West Coast, including the AO (Guan and Waliser, ); ENSO (Guan and Waliser, ; Mundhenk et al, ; Kamae et al, ), the MJO (Ralph et al, ; Guan et al, ; Mundhenk et al, ; Mundhenk et al, ), and the PNA (Guan and Waliser, ), while it has also been shown that the relationship between the MJO and atmospheric river activity is further modulated by the phase of other HCIs, such as ENSO (Mundhenk et al, ) and the QBO (Baggett et al, ; Mundhenk et al, ). Additional investigation is required in order to shed more light on the impact of the lower‐frequency variability of the MJO, ENSO, and the EAWR, on long‐term precipitation variability along both coasts and the potential modulation of the these HCIs by the other dominant interannual modes of variability as mentioned above.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Recently, Mizuta et al (2017) performed large ensemble 4-K warming climate and historical climate experiments (the database for Policy Decision making for Future climate change: d4PDF) using a 60-km atmospheric general circulation model (AGCM) and 20-km regional model. This data set has enabled examination of future change in extreme events at the end of the century such as tropical cyclone activity (Yoshida et al, 2017), extreme snow events (Kawase et al, 2016), East Asian monsoon precipitation , Northern Hemisphere blocking (Matsueda & Endo, 2017), and the reproducibility of atmospheric rivers in the d4PDF historical climate experiment (Kamae et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The ensemble simulations were developed with random initial and SST perturbations (Hirahara et al 2014). In this study, a 10-member ensemble mean was examined to reduce the effect of atmospheric internal variability (Kamae et al 2017a(Kamae et al , 2017b.…”
Section: Agcm and Current Climate Simulationmentioning
confidence: 99%
“…Hawkins andSutton 2009, Thompson et al 2015) by using large-member ensemble simulations (e.g. Deser et al 2012, Hagos et al 2016, Kamae et al 2017a, 2017b for quantitative evaluation of forced response to global warming.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation